Fibrin glue versus autologous platelet-rich fibrin - comparison of effectiveness on the cohort of patients with fistula-in-ano undergoing video-assisted anal fistula treatment - Riju Ramachandran; Vaishnavi Gunasekharan; Anoop Vasudevan Pillai; Suyambu Raja; Anjaly S Nair (Journal of Minimal Access Surgery, 2022)
Context: Minimally invasive sphincter preserving procedures like ligation of intersphincteric fistula tract (LIFT) and video-assisted anal fistula treatment (VAAFT) are being increasingly used in the treatment of fistula-in-ano. The addition of adjuncts like fibrin glue has improved the results for VAAFT. Our unit has used platelet-rich fibrin (PRF) as an innovative adjunct for VAAFT. Aims: To compare the effectiveness of two different adjuncts, fibrin glue and autologous PRF, used to fill the treated fistula tracts following VAAFT. Settings and Design: Retrospective observational study on a cohort of patients undergoing VAAFT at a tertiary centre between 2015 and 2020 comparing two adjuncts used with VAAFT procedure. Subjects and Methods: Data of patients who underwent VAAFT for fistula-in-ano were obtained from the hospital database. Group A included patients treated with fibrin as adjunct and PRF as adjunct in Group B. Patients were followed up at 1, 3 and 6 months post-operatively and by a telephonic interview in 2020 to ascertain recent status. All data were entered into an excel sheet. Statistical Analysis Used: Data were analysed using SPSS V20 to test the statistical significance of the difference in the mean healing time between two groups, Mann–Whitney U-test was used and for age, Student's t-test was used. Results: There were 41 patients in Group A and 24 in Group B. There was a significant reduction in recurrence rate in Group B (p = 0.032) and in those patients who had a single internal opening (p = 0.045), single external opening (p = 0.03) and complex tracts (p = 0.033). PRF was cheaper than Fibrin glue. Conclusions: PRF is more effective and economical with lower recurrence rates.